L’activité réflexive des agents de terrain lors d’un dispositif de formation hybride qui intègre de la réalité virtuelle - Artémis Drakos; Jacques Theureau; Geneviève Filippi; Simon Flandin; Germain Poizat (Activités)
This article examines the reflexive activity of field agents in a training device created for the nuclear industry. Designed by the researchers and a trainer, this device, known as scenario-inquiry, is intended to help trainees gain an understanding of the spatial and functional characteristics of a complex industrial building, essential knowledge for their future job as field operators. The device might be described as hybrid in the sense that it combines various teaching spaces and methods (a virtual environment for trainees to browse, an onsite training workplace, a traditional classroom) as well as several technical objects (a complete 3D digital model of the building, full-scale models of valves and operational technical documentation used in work situations). The semio-logical analysis stemming from the course-of-action framework, and its dialogical relationship with Peirce’s semiotics, serve as the foundation for understanding the operators’ training activities. Abduction, deduction, and induction are the three types of inference that define their interpretative activity when using the scenario-inquiry device. Abductive inference is the process of formulating explanatory hypotheses enabling the discovery and creation of novelty. Our results indicate (i) the determining role of abductive reasoning in the creation, reinforcement, invalidation and connection of knowledge, and (ii) the essential role of analogies in the linking of acquired knowledge and new knowledge by abduction. This article offers the opportunity to critically examine training scenarios that place emphasis on inductions and deductions. Offering educational resources that support abductive reasoning—such as “curiosity laboratories,” which are learning settings that inspire people to explore and go beyond the boundaries of what is expected of them—would be ideal. This will encourage trainees to switch between a range of semiotic registers.